Managerial perspectives of scaling up robotic-assisted surgery in healthcare systems: A systematic literature review - Ravichandran Anitha; Komattu Chacko John; Gnanadhas Jabarethina (Laparoscopic, Endoscopic and Robotic Surgery, 2024)
Objectives: Robotic-assisted surgery (RAS) is a minimally invasive technique practiced in multiple specialties. Standard training is essential for the acquisition of RAS skills. The cost of RAS is considered to be high, which makes it a burden for institutes and unaffordable for patients. This systematic literature review (SLR) focused on the various RAS training methods applied in different surgical specialties, as well as the cost elements of RAS, and was to summarize the opportunities and challenges associated with scaling up RAS. Methods: An SLR was carried out based on the Preferred Reporting Items for Systematic reviews and Meta-Analyses reporting guidelines. The PubMed, EBSCO, and Scopus databases were searched for reports from January 2018 through January 2024. Full-text reviews and research articles in the English language from Asia-Pacific countries were included. Articles that outlined training and costs associated with RAS were chosen. Results: The most common training system is the da Vinci system. The simulation technique, which includes dry-lab, wet-lab, and virtual reality training, was found to be a common and important practice. The cost of RAS encompasses the installation and maintenance costs of the robotic system, the operation theatre rent, personnel cost, surgical instrument and material cost, and other miscellaneous charges. The synthesis of SLR revealed the challenges and opportunities regarding RAS training and cost. Conclusions: The results of this SLR will help stakeholders such as decision-makers, influencers, and end users of RAS to understand the significance of training and cost in scaling up RAS from a managerial perspective. For any healthcare innovation to reach a vast population, cost-effectiveness and standard training are crucial.